Synthesis, characterization, microstructure determination, thermal studies of poly (N-vinyl pyrrolidone-maleic anhydride-methyl methacrylate). Issue 4 (3rd April 2018) - Ajithkumar, M. P.; Yashoda, M. P.; Prasannakumar, S.; Sruthi, T. V.; Sameer Kumar, V. B.
ABSTRACT: Synthesis of Poly (N-vinyl pyrrolidone-maleic anhydride-methyl methacrylate) terpolymer using azobisisobutyronitrile in 1, 4-dioxan is described. The polymers with different composition were synthesized and characterized using FTIR, 1 HNMR, 13 NMR, TGA and DSC techniques. The monomer-monomer interactions were studied using Finemann-Ross and Kelen-Tudos methods by calculating the reactivity ratio. The reactivity ratio r1 and r2 with respect to methyl methacrylate and N-vinylpyrrolidone-maleic anhydride complexomer are found to be 6.05 and 0.06 respectively. The study showed methyl methacrylate have higher reactivity than N-vinyl-2-pyrrolidone-maleic anhydride complex, i.e., the terpolymer contained methyl methacrylate in higher ratio. The thermal stability of poly (N-vinyl pyrrolidone-maleic anhydride-methyl methacrylate) was 165°C and the glass transition temperature was found to increase from 153°C to 182°C as MMA concentration increase. The studies indicate the activity of the polymer to inhibit bacterial growth is very poor.